PENERAPAN PEMBELAJARAN BAHASA INDONESIA BERBASIS KEGIATAN PRAMUKA - Evi dalilah; Anastya Basyith Ad Dauwi; Dheeva Softya Khazahratul Jannah; Decenni Amelia (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to explore the integration of responsibility and discipline values through Indonesian language learning based on Scout activities. The background of the research highlights the urgency of character education in Indonesia, which is not only focused on academic achievement but also on strengthening students’ moral values. Scout activities, as a form of non-formal education, offer an effective platform to instill positive character traits. Using a descriptive qualitative approach, this research analyzes the experiences and perceptions of students participating in Scout-based learning. The findings show that integrating Scout activities into Indonesian language lessons significantly enhances students’ motivation, responsibility, and discipline. The process encourages students to develop collaborative skills, communicate effectively, and build self-confidence. Furthermore, it was found that the practical and contextual learning environment of Scouts supports students in internalizing values more meaningfully. This study contributes to the development of character-based learning models and provides insights for educators to optimize extracurricular activities as a medium for character education in formal learning.